Applications of jet–jet/film impingement for atomization enhancement - He, Chengming; Feng, Zehao; Zhang, Zhenyu; He, Zhixia (Frontiers in Physics, 2025)
This mini-review mainly focuses on the fundamental problem of jet–jet/film impingement exhibiting superior fragmentation and atomization characteristics compared to single-jet injection; this has been widely used in agricultural irrigation and combustion propulsion systems. First, it presents the main controlling parameters and spray characteristic for both jet–jet and jet–film configurations, analyzes the breakup mechanisms, and points out the coupling between jet fragmentation processes and collision-induced or externally imposed vorticity fields. Then, the atomization enhancement of jet–jet or jet–film impingement is explained from the aspects of vortex generation, evolution, identification, and the interactions between vorticity fields and spray fields. Finally, representative applications of jet–jet/film impingement in agricultural engineering and aerospace engineering are introduced so as to achieve spatially uniform spray distribution and efficient fuel/oxidizer mixing characteristics. Future advancements require breakthroughs in cross-scale vortex–ligament interaction diagnostics and intelligent control of variable-viscosity fluids to promote deep implementation of this technology in clean energy systems.